Cost-effectiveness of Investment in End-of-Life Home Care to Enable Death in Community Settings. Issue 8 (August 2020) - Isenberg, Sarina R.; Tanuseputro, Peter; Spruin, Sarah; Seow, Hsien; Goldman, Russell; Thavorn, Kednapa; Hsu, Amy T.
Abstract : Background: Many people with terminal illness prefer to die in home-like settings—including care homes, hospices, or palliative care units—rather than an acute care hospital. Home-based palliative care services can increase the likelihood of death in a community setting, but the provision of these services may increase costs relative to usual care. Objective: The aim of this study was to estimate the incremental cost per community death for persons enrolled in end-of-life home care in Ontario, Canada, who died between 2011 and 2015. Methods: Using a population-based cohort of 50, 068 older adults, we determined the total cost of care in the last 90 days of life, as well as the incremental cost to achieve an additional community death for persons enrolled in end-of-life home care, in comparison with propensity score–matched individuals under usual care (ie, did not receive home care services in the last 90 days of life). Results: Recipients of end-of-life home care were nearly 3 times more likely to experience a community death than individuals not receiving home care services, and the incremental cost to achieve an additional community death through the provision of end-of-life home care was CAN$995 (95% confidence interval: −$547 to $2392). Conclusion: Results suggest that a modest investment in end-of-life home care has the potential to improve the dying experience of community-dwelling older adults by enabling fewer deaths in acute care hospitals. Abstract : Supplemental Digital Content is available in the text.